Routes for the Circulation and Exchange of Salt in the Province of Tunja, second half of the XVI century - Acuña Rodríguez, Blanca Ofelia (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This paper examines the way in which trade routes for circulation of salt in the Province of Tunja contributed to the coniguration of an extensive economic territory, integrating the provinces of Santa Fé, Pamplona and Tunja in the New Kingdom of Granada during the XVI century. The research initiates from a historiographic relection related to the circulation and commerce of salt, its transport media and trade routes used by the natives and spaniards. These routes consolidated an economic space mediated by the production and distribution of salt, which transformed the Province of Tunja into an axis that articulated relations between salt production locations in the province of Santa Fe and its consumers in the provinces of Tunja and Pamplona. This regional articulation enabled the circulation of products from different thermal loors, as well as the integration of an ample colonial territory. The location of Tunja as a crossroads between the Provinces of Santafe, Pamplona and the San Juan Plains, made this city and its surroundings into an attraction for Spanish settlement. Likewise, during the second half of the XVI century, this condition triggered the organization, throughout the province of Tunja, of different places of lodging, sale and resale of products of the earth as well as imports from Spain, for the sustenance and supply of basic needs. These places enabled the circulation and exchange of local products such as salt, hayo, cotton, blankets and others.